Clinical Characteristics of Children With SARS-CoV-2 Infection in a Hospital in Latin America - Niño-Serna, Laura F.; López-Barón, Eliana; Maya Ángel, Isabel Cristina; Tamayo-Múnera, Carolina (Frontiers in Pediatrics, 2022)
Objective COVID-19 infections have shown a different behavior in children than in adults. The objective of this study was to describe the clinical characteristics and severity of SARS-CoV-2 infection in pediatric patients seen at a reference hospital in Colombia. Method A descriptive, observational study in patients under the age of 18 years with a positive test for SARS-CoV-2 infection (RT-PCR or antigen) between April 2020 and March 2021. Multiple variables were studied, including demographic data, clinical characteristics, lab measurements, treatments administered, intensive care unit admission, and mortality. Results A total of 361 patients were included of whom 196 (54%) were males. The median age was three years. Of all the patients, 65 (18%) were asymptomatic. The majority of patients had no comorbidities (n=225; 76%). In those who were symptomatic (n=296;82%), the most frequent complaints were fever (n=178, 60%), nasal congestion (n=164; 55%) and cough (n=149;50%). Chest x-rays were normal in 73 patients (50%). When abnormalities were found, interstitial (29%) and alveolar (12%) patterns were the most prevalent. One hundred and fifty-seven children (53%) required general ward hospitalization, and 24 patients (8%) required pediatric intensive care admission. The global mortality was 0.8% (3 patients). Conclusions The majority of cases were asymptomatic or mild. However, a significant percentage of patients required general ward admission. The main symptom of COVID-19 infections in newborns was apnea. A second COVID-19 RT-PCR may be necessary to detect infections in critically ill patients with a high clinical suspicion of the disease if an initial test was negative.